Microalgae-derived hydrogen production towards low carbon emissions via large-scale outdoor systems. (November 2022) - Sung, Young Joon; Yu, Byung Sun; Yang, Ha Eun; Kim, Dong Hoon; Lee, Ju Yeon; Sim, Sang Jun
Graphical abstract: Highlights: Studies are introduced to reduce carbon emissions under large-scale culture system. Downstream systems to maximize microalgae-based biomass productivity were reviewed. Efficient biohydrogen production strategies that reduce carbon emissions are needed. The methods of hydrogen production and storage from microalgae are presented. Additional cost-effective strategies are needed to mass-produce hydrogen. Abstract: Hydrogen as a clean fuel is receiving attention because it generates only water and a small amount of nitrogen oxide upon combustion. Biohydrogen production using microalgae is considered to be a highly promising carbon–neutral technology because it can secure renewable energy while efficiently reducing CO2 emissions. However, previous studies have mainly focused on improving the biological performance of microalgae; these approaches have struggled to achieve breakthroughs in commercialization because they do not heavily consider the complexity of the entire production process with microalgae, including large-scale cultivation, biomass harvest, and biomass storage. This work presents an in-depth analysis of the state-of-the-art technologies focused on large-scale cultivation systems with efficient downstream processes. Considering the individual processes of biohydrogen production, strategies are discussed to minimize carbon emissions and improve productivity simultaneously. A comprehensive understanding of microalgae-derived biohydrogen production suggests future directions for realizing environmental and economic sustainability.